Moving Maritime Boundaries: Changes in Coastal Land Sovereignty, River Courses, Sea Levels, and Maritime Delimitation Law - Tzeng, Peter (UI Scholars Hub, 2018)
In February 2009, the International Court of Justice rendered a judgment delimiting a maritime area of the Black Sea between Romania and Ukraine. The very next month, Indonesia and Singapore concluded a treaty delimiting their maritime boundary in the western part of the Strait of Singapore. Although these two delimitations occurred by different means (adjudication and negotiation), years later, they raise the same question: can a subsequent event move a maritime boundary? As a matter of lex lata, the answer is probably “no”. As a matter of lex ferenda, however, this Article questions whether the law governing land boundaries should also apply to maritime boundaries in light of key differences between land and maritime boundaries.